Optical, Photocatalytic and Magnetic Properties of ZnO Nanostructures Prepared by Thermal Decomposition - My, Kim Thi Hue; Son, Vu Xuan; Duc Tien, Do; Lam, Nguyen Dinh; Giang, Do Thi Huong; Bich, Do Danh; Quynh, Luu Manh; Thang, Pham Duc; Toan, Dang Ngoc; The Long, Phan (VNU Journal of Science: Mathematics - Physics, 2025)
ZnO nanostructures have been fabricated by annealing zinc acetate dihydrate at different temperatures ( T an ). Thermogravimetric analysis, and XRD and Raman studies indicate ZnO crystals formed at above 250 o C. An increase of T an would enhance the XRD intensity and number of Raman modes characteristic of hexagonal ZnO. Below 700 o C, the samples are mainly nanorods with the diameters and lengths of 50 –100 nm and 250 – 500 nm, respectively. As T an increases from 700 to 1,200 o C, nanorods transform to irregular particles with average sizes of 0.2 – 2 mm. This influences the intensity ratio of UV-to-visible emissions. Though all the samples exhibit diamagnetism, several samples with T an = 500 – 700 o C have additionally weak ferromagnetic order. Assessing RhB photodegradation has demonstrated the T an = 300 o C sample showing the best photocatalyticity.